Go to church or die in prison: PPs with bare institutional nouns in the history of English - Sommerer, Lotte; Zehentner, Eva (Folia Linguistica, 2025)
This paper traces the diachronic development of prepositional phrases (PPs) with bare institutional/location nouns (e.g. go to church, stay in bed, die in prison) from Middle English to Late Modern English. Based on a dataset of 2,249 instances extracted from the Penn Parsed Corpora of Historical English (PPCME2, PPCEME, PPCMBE2), we investigate changes in the usage of these constructions (i.e. formal and functional features). One question addressed is why a definite determiner is apparently ‘missing’ in these constructions (died in prison rather than died in the prison) and what kind of semantic interpretation this lack of overt definiteness marking triggers. Moreover, we assess whether there is evidence of these PPs becoming increasingly integrated into the extended verb phrase, by zooming in on the patterns’ semantic functions and formal features. By using collostructional analyses as well as by fitting a conditional random forest model, we show that different constructional types can be identified, which differ regarding the association strength between the elements involved as well as regarding their preferred semantic function, among other things. These results are then discussed from a usage-based, cognitive constructional perspective, indicating that the constructions at hand force us to revisit traditional assumptions about phrase structure boundaries and compositionalit
Keywords: bare PP-patterns; compositionality; construction grammar; history of English; phrase boundaries